2022
DOI: 10.1002/anie.202208185
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo‐ and Enantioselective Inverse‐Electron‐Demand Diels–Alder Cycloaddition between 2‐Pyrones and Acyclic Enol Ethers

Abstract: A broadly applicable diastereo-and enantioselective inverse-electron-demand Diels-Alder reaction of 2-pyrones and acyclic enol ethers is reported herein. Using a copper(II)-BOX catalytic system, bridged bicyclic lactones are obtained in very high yields (up to 99 % yield) and enantioselectivities (up to 99 % ee) from diversely substituted 2-pyrones and acyclic enol ethers. Mechanistic experiments as well as DFT calculations indicate the occurrence of a stepwise mechanism. The synthetic potential of the bridged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…(ii) The C–O bond coupling between fragments 4 and 5 will also be an important challenge, as the formation of β-keto enol ethers typically requires the use of excess hydroxy partner, which makes it unsuitable for fragment coupling . (iii) The challenge of enantioselective IEDDA reaction involving 2-pyrones and acyclic enol ethers for the synthesis of bridged bicyclic lactones was recently tackled by our group through the development of a new synthetic methodology. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The C–O bond coupling between fragments 4 and 5 will also be an important challenge, as the formation of β-keto enol ethers typically requires the use of excess hydroxy partner, which makes it unsuitable for fragment coupling . (iii) The challenge of enantioselective IEDDA reaction involving 2-pyrones and acyclic enol ethers for the synthesis of bridged bicyclic lactones was recently tackled by our group through the development of a new synthetic methodology. , …”
mentioning
confidence: 99%
“…However, all our attempts to prepare the 2-pyrone derivative 6a proved unsuccessful (see Scheme S1-1–S1-3 in the Supporting Information). Therefore, we applied the IEDDA reaction developed by our group with pyrone 6b and benzyl enol ether 7 . The synthesis of (−)-12 could be efficiently performed in the multigram scale.…”
mentioning
confidence: 99%
“…Therefore, the development of an efficient asymmetric catalytic system to promote this reaction under mild reaction conditions is highly desirable. Although great achievements have been made very recently for the development of enantioselective IEDDA reactions of 2-pyrones, [18][19][20][21][22][23][24][25][26] the reaction using a cis-phenyl vinyl selenide as the dienophile remains elusive. Only two related examples have been reported.…”
mentioning
confidence: 99%
“…Recently, the Tang group has demonstrated that side arms on the bisoxazoline framework have great influence on both the reactivity and stereocontrol. 29 This strategy was then employed successfully by us [20][21][22] and de la Torre [25][26] S2). To our great delight, it was revealed that L11 with a 3,5-bis(trifluoromethyl)benzyl group dramatically improved the enantioselectivity, affording 3a in 95% yield and 88% ee (Table 1, entry 11).…”
mentioning
confidence: 99%
See 1 more Smart Citation